2012
DOI: 10.1007/s10725-012-9774-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of Amaranthus retroflexus L. seeds to gibberellic acid, ethylene and abscisic acid depending on duration of stratification and burial

Abstract: Freshly harvested, dormant seeds of Amaranthus retroflexus were unable to germinate at 25 and 35°C. To release their dormancy at the above temperatures, the seeds were stratified at a constant temperature (4°C) under laboratory conditions or at fluctuating temperatures in soil or by outdoor burial in soil. Fully dormant, or seeds stratified or buried

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It is clear from our results that cold stratification had a significant effect on seed dormancy breakage. This is consistent with earlier reports of common weeds in which seed dormancy is broken by cold stratification, for example A. retroflexus (Kępczyński & Sznigir, ), C. album (Baskin & Baskin, ; Matsuo & Kubota, ), C. suecicum (Scholz) Murr. (Milberg & Andersson, ) and C. rubrum L. (Galinato & Van Der Valk, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is clear from our results that cold stratification had a significant effect on seed dormancy breakage. This is consistent with earlier reports of common weeds in which seed dormancy is broken by cold stratification, for example A. retroflexus (Kępczyński & Sznigir, ), C. album (Baskin & Baskin, ; Matsuo & Kubota, ), C. suecicum (Scholz) Murr. (Milberg & Andersson, ) and C. rubrum L. (Galinato & Van Der Valk, ).…”
Section: Discussionsupporting
confidence: 92%
“…A range of environmental factors, such as temperature, light and soil chemistry, have been reported to play a role in regulating seed dormancy release and germination in these species (Baskin & Baskin, ). For example, cold stratification could release seed dormancy of A. retroflexus (Kępczyński & Sznigir, ), C. album (Baskin & Baskin, ), C. hybridum (Hu et al ., ) and Setaria glauca (Amini et al ., ), depending on stratification duration (Kępczyński & Sznigir, ; Baskin & Baskin, ; Amini et al ., ) and seed sources (Amini et al ., ). However, no studies have reported the effects of soil moisture content during cold stratification on the dormancy status of these species.…”
Section: Introductionmentioning
confidence: 99%
“…1; Table 2). Stratification enhanced the response to GA 3 and ethylene only in the darkness (Kępczyński and Sznigir 2013, Table 2). Gases, NO ?…”
Section: Control Germination Of Dormant Seeds In the Lightmentioning
confidence: 99%
“…Dormancy of these seeds can be removed by means of burial in late autumn and winter (Egley 1989;Kępczyński and Sznigir 2013). Likewise, cold stratification may release dormancy in these seeds, however, less effectively than burial (Kępczyński and Sznigir 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation